Behavioral flexibility in Wasmannia auropunctata (Hymenoptera: Formicidae). Issue 4 (26th August 2021) - Ortiz-Alvarado, Yarira; Fernández-Casas, Rafael; Ortiz-Alvarado, Carlos A; Diaz-Iglesias, Emily; Rivera-Marchand, Bert
Abstract: Worker division of labor is a defining trait in social insects. Many species are characterized by having behavioral flexibility where workers perform non-typical tasks for their age depending on the colony's needs. Worker division of labor and behavioral flexibility were examined in the little fire ant Wasmannia auropunctata (Roger, 1863), for which age-related division of labor has been found. Young workers perform nursing duties which include tending of brood and queens, and colony defense, while older workers forage. When nurses were experimentally removed from the colony, foragers were observed carrying out nursing and colony defense duties, yet when foragers were removed nurses did not forage precociously. We also administered juvenile hormone analog, methoprene, to workers. When methoprene was applied, foragers increased their nursing and defense activities while nurses became mainly idle. The behavioral flexibility of foragers of the little fire ant may be evidence of an expansion of worker's repertoires as they age; older workers can perform tasks they have already done in their life while young individuals are not capable of performing tasks ahead of time. This may be an important adaptation associated with the success of this ant as an invasive species.